CTNI-51. FEASIBILITY AND SAFETY OF NEUROSURGICAL RESECTION AND INTRA-OPERATIVE RADIATION THERAPY USING THE XOFT AXXENT ELECTRONIC BRACHYTHERAPY SYSTEM AND BEVACIZUMAB IN RECURRENT GLIOBLASTOMA. (14th November 2022) - Wagle, Naveed; Barkhoudarian, Garni; Chaiken, Lisa; Wollman, Robert; Sharma, Akanksha; Carrillo, Jose; Nguyen, Minh; Truong, Judy; Chow, Jared; Chacon, Emma; Kesari, Santosh
Abstract: Glioblastoma (GBM) is the most common and aggressive primary brain tumor. External beam radiation therapy (EBRT) is widely recognized as an effective treatment for primary GBM. EBRT applied after GBM resection is associated with an increase in overall survival. Beyond upfront therapy with radiation and temozolomide chemotherapy, there is no standard therapy that has been proven effective. Re-irradiation with ERBT is minimally effective and with significant comorbidities. Our study uses IORT at the time of re-resection in patients who have recurrent, operable GBM after failure of who received primary EBRT and temozolamide in their first course of treatment. IORT allows the delivery of a large effective radiation dose applied directly to the tumor bed at the time of resection. This affords direct radiation to be delivered to the micro- and macroscopic tumor remnants in the vicinity of the resection cavity immediately following gross resection. In contrast, the more distant, surrounding brain tissue does not receive high radiation exposure. This Phase II study continues to accrue subjects with the primary endpoint of overall survival and several secondary endpoints that includes progression free survival, quality of life, and adverse events/safety. To date, five patients have been treated on this protocol. The technical feasibility and safety of administering intraoperative radiation with the Xoft System has been established in this cohort. Preliminary GLIOX Trial findings demonstrate the safety and feasibility of using the Xoft Axxent® Electronic Brachytherapy System to administer intracranial radiation during resection of recurrent glioblastomas. We will report new and expansive study results to include these early findings.